(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
Gender, as both a theoretical construct and a lived reality, remains a contested and evolving concept. Following a review method along with scientific readings, this paper articulates that feminist theorists have critically engaged with the term, challenging its binary understanding and emphasizing its fluidity. Gender is not merely a social identity but intersects with law, politics, and culture, shaping societal structures and individual experiences. The origins of rigid gender roles can be traced back to the Victorian era, which reinforced the division of public and private spheres—assigning men to public engagement and women to domestic responsibilities. In deeply patriarchal societies like Nepal, gender discrimination persists, perpetuated by ingrained stereotypes and biases that begin in early childhood and extend to professional and leadership domains. Notably, women’s internalization of societal norms further reinforces gender inequality. Despite progress, global statistics indicate that only about 25 percent of leadership positions are occupied by women, reflecting continued disparities in compensation and executive opportunities. Given the deeply embedded nature of gender discrimination, education emerges as a fundamental tool in dismantling stereotypes and fostering gender equality.